2020
DOI: 10.1021/acs.chemmater.9b04117
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active Rhenium-, Ruthenium-, and Iridium-Based Dichalcogenide Electrocatalysts for Oxygen Reduction and Oxygen Evolution Reactions in Aprotic Media

Abstract: Transition metal dichalcogenides (TMDCs) have garnered much attention recently due to their remarkable performance for different electrochemical systems. In this study, we report on the synthesis and catalysis of less studied TMDC nanoflakes (NFs) with a design space comprised of three transition metals (rhenium, ruthenium, and iridium) and three chalcogens (sulfur, selenium, and tellurium) for the oxygen reduction and evolution reactions (ORR and OER) in an aprotic hybrid electrolyte containing 0.1 M lithium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 72 publications
1
14
0
Order By: Relevance
“…In particular, ReS 2 and ReSe 2 are of interest more than the others because they are predicted to be superior to Cu. Furthermore, these materials are known to be stable under reduction environments. We also confirm the stability of the candidate materials, namely, SnSe 2 , ReS 2 , and ReSe 2 , by calculating oxidation/reduction leaching potential (Figure S5). …”
Section: Resultssupporting
confidence: 56%
“…In particular, ReS 2 and ReSe 2 are of interest more than the others because they are predicted to be superior to Cu. Furthermore, these materials are known to be stable under reduction environments. We also confirm the stability of the candidate materials, namely, SnSe 2 , ReS 2 , and ReSe 2 , by calculating oxidation/reduction leaching potential (Figure S5). …”
Section: Resultssupporting
confidence: 56%
“…42 In this study, we found that indium iodide (InI 3 ) and indium bromide (InBr 3 ) RMs are extremely effective in a system comprised of a hybrid electrolyte of dimethyl sulfoxide (DMSO) and 1-ethyl-3-methylimidazolium tetrafluoroborate ( E M I M -B F 4 ) i o n i c l i q u i d w i t h l i t h i u m b i s -(trifluoromethanesulfonic)imide (LiTFSI) salt along with a molybdenum disulfide (MoS 2 ) cathode that exhibit high exchange current densities during oxygen reduction and evolution reactions (ORR/OER). 43 Previous studies 44,45 have used InI 3 and InBr 3 next to multiwalled carbon nanotube cathodes, in a pure oxygen environment. In the case of InBr 3 , it was reported that the battery cycled up to 206 cycles with a small current density of 0.25 A g −1 , while for the InI 3 case, only 50 and 40 cycles were achieved with current densities of 0.5 and 1 A g −1 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Majidi et al developed ReS 2 by chemical vapour transport methods and studied the OER activity in an aprotic solvent. 20 They exhibited the highest current density of 6.89 mA cm −2 , which signifies that the OER activity is remarkably lower compared to the activity in 1 M KOH. Tian et al reported a high OER activity of 280 mV overpotential at 10 mA cm −2 current density for Fe-doped NiS 2 /MoS 2 composites.…”
mentioning
confidence: 92%
“…It is worth comparing the OER activity of Ni d (5)S v @ReS 2 NS with the other reported metal sulphides and the results are summarized in Table S1 (ESI †). However, very few reports demonstrate the OER 20 They exhibited the highest current density of 6.89 mA cm À2 , which signifies that the OER activity is remarkably lower compared to the activity in 1 M KOH. Tian et al reported a high OER activity of 280 mV overpotential at 10 mA cm À2 current density for Fe-doped NiS 2 /MoS 2 composites.…”
mentioning
confidence: 95%
See 1 more Smart Citation